Ceramah Agama dalam Acara Pondok Ramadhan di SMKN 1 Arosbaya - Ach. Ghufron; Ahmad Bahrudin (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
Religious Lecture at SMKN 1 Arosbaya. The formulation of the problem raised in this community service activity is related to the weak understanding of the Arosbaya community about religion, especially in ubudiyah issues. To find alternative solutions to the above, religious counseling was held. The objectives of this activity are: 1. To equip the Arosbaya community with religious knowledge. 2. Equip the community, especially the students of SMKN 1 Aroesbaya so that they can know and understand the main points of Islamic law in detail and comprehensively, both in the form of naqli and aqli propositions, implementing and practicing the provisions of Islamic law correctly. The problem-solving framework designed in this activity in the form of implementing these counseling activities are: 1. Holding weekly religious lectures or wirid 2. teaching reading the Qur'an 3. helping to change people's behavior in a better direction 4. holding religious activities that involve the whole community as activities in it 5 .. Evaluation of counseling results. Based on interviews, questions and answers and direct observation during the activity, this community service activity yielded the following results: first, increased knowledge and understanding of the Arosbaya community, second, equipping the Arosbaya community with religious knowledge related to ubudiyah, third, increasing the knowledge and knowledge of the community, formation of a religious society.